THE RELEVANCE OF PICTURES AS MEDIA IN THEMATIC LEARNING BOOK WITH PLURALISM VALUES IN INDONESIA - Suwardi., (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2017)
Indonesian people are very plural in ethnics, races and religions. In Indonesia, there are about 931 ethnics, 731 local languages, and 6 religions. This situation may cause horizontal conflicts in Indonesia. Historically, there were some outstanding communal conflicts in Indonesia, happening in Ambon, Maluku, Poso, Kalimantan, Sampang Madura, Cikeusik Banten, Papua, Nusa Tenggara, Talang Sari Samarinda, etc. Education has a strategic role to prevent the conflicts among people by implementing the pluralism values to students. This study aims to investigate the relevance of pictures in the thematic learning book for the first grade students of elementary school with the pluralism values in Indonesia. This is a descriptive quantitative research. The objects of this research are pictures as media in the thematic learning book used by the students in the first grade of elementary school. There are 222 set of pictures. Picture in one page is considered as a set of picture. The data are analyzed in a descriptive statistic way using percentile formula. The findings of this research show that there are 128 (57.66%) pictures in the learning book are relevant to the values of ethnic and religion plurality.